Exploring typologies of appraisals, involvement, and distress in type 2 diabetes family members. (February 2023) - Novak, Josh R; August, Kristin J; Kavookjian, Jan; Whitley, Heather; Burnett, Donna
The present study conducted a latent profile analysis from a US national sample of 446 family members to identify and predict unique clusters of family members' PWD illness appraisals, involvement, and psychological distress. Time since diagnosis, diabetes adherence, the relationship with the PWD, age, gender, race/ethnicity, income, and economic pressure were included as predictors. Class membership was used to predict the family members' own health behaviors (sleep quality, days of physical activity, and diet quality). Results revealed four distinct classes: Moderately Concerned, Involved, and Distressed (32.51%), Least Concerned, Distressed, and Involved (27.13%), Less Concerned and Distressed, Moderately Involved (23.77%), and Most Concerned, Involved, and Distressed (16.82%). The significant predictors and outcomes of class membership revealed interesting patterns in associations with class membership. Consequently, in addition to involving family members, health promotion and intervention efforts must consider the psychological health and illness appraisals of family members rather than a one-size-fits-all approach.